The road after cancer: biomaterials and tissue engineering approaches to mediate the tumor microenvironment post-cancer treatment - Westwood, Lorna; Nixon, Iain J.; Emmerson, Elaine; Callanan, Anthony (Frontiers in Biomaterials Science, 2024)
Cancer affects tens of millions of the world’s population each year with a stark mortality rate. It is well established that in order to be effective in treating solid tumor cancers, the current treatment methods used often sacrifice surrounding healthy tissue and cause damage at the site of treatment, inducing changes to the surrounding microenvironment. These changes to the microenvironment can lead to adverse side effects as well as long-term damage which continues to have a detrimental impact on the patient’s quality of life, even after remission. It is believed that by modulating the tumor microenvironment (TME) post-treatment, not only may the efficacy of current treatments be improved, but such associated negative side effects, as well as further complications arising from treatment, including metastasis, have the potential to be reduced. Mediating the microenvironment is also considered to aid in repairing the damaged site post-treatment, subsequently making the conditions more favourable for promoting regenerative processes. This review provides a brief overview of the alterations in the TME resulting from the three main cancer treatments – chemotherapy, radiation therapy and surgery – and the most common tissue engineering methods currently used in an attempt to mediate the TME post-cancer therapy. Furthermore, it investigates new emerging technologies within this field and the progress of such methods in terms of reaching the clinical setting.